MENINGKATKAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN BOLA ESTAFET PADA ANAK USIA 5-6 TAHUN DI TK PERTIWI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - ', Rosila; ', Mahdum; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
bstract : Learning to use the principle of early childhood learning, play, and sing. Early childhood learning to be realized in a way that can make children active, happy, free to choose. Children learn through interaction with tools and supplies as well as a human game. Gross motor development is very important for children kindergarten for gross motor development affects the development of the other. Motor skills of kindergarten children will not develop without the maturity of motor control, motor control will not be optimal without physical fitness, physical fitness can not be achieved without physical exercise. TK Pertiwi Benai Benai located in the Village SubDistrict of Benai, this is one of the early childhood education institutions are experiencing some problems with regard to the learning gross motor skills in children with methods of game ball relay. Problem 1. Some children may not be able to observance perturan game. 3. Some children are difficult to perform motion bounding. 2. Child difficult to throw directionally. 3. Children are not able to catch the ball. In addition there are some children who still lack the coordination capabilities such as hand and eye coordination. Based on the formulation of the problem that has been presented, it can be seen the purpose of this study was to determine the increase in gross motor skills of children aged 5-6 years in kindergarten through ball game Pertiwi relay. How is the implementation of a ball game relay to improve gross motor skills of children aged 5-6 years in kindergarten Pertiwi and knowing how high the increase in gross motor skills of children aged 5-6 years through the game ball in the kindergarten relay relay PertiwiDengan ball game can improve gross motor skills of children ages 5 -6 years in TK Pertiwi Benai Subdistrict Regency Kuantan Singingi especially on the aspect of speed, agility, and hand-eye coordination in children TK Pertiwi Benai Regency Kuantan Singingi. The game is done by following the steps to play a relay which was carried out so that the results become more optimal, it is seen when a child is asked to go from house to fhoto copy to memotocopy book, of a copy home turns out the child is able to do it well and correctly capability children are developing as expected (BSH) which saw gross motor skills of children before treatment only (30.27%) and then after being given treatment (cycle 1) turns gross motor skills of children increased first cycle that an average of 43.69 and continued an increase in Cycle II reached an average percentage of 75.36%.Keywords: Game Ball Relay, Rough Motoric